Efficacy of a new once-daily long-acting inhaled β2-agonist indacaterol versus twice-daily formoterol in COPD. Issue 6 (3rd June 2010) - Dahl, Ronald; Chung, Kian Fan; Buhl, Roland; Magnussen, Helgo; Nonikov, Vladimir; Jack, Damon; Bleasdale, Patricia; Owen, Roger; Higgins, Mark; Kramer, Benjamin
Abstract : Background: Indacaterol is a long-acting inhaled β2 -agonist (LABA) for the treatment of chronic obstructive pulmonary disease (COPD). In previous studies, indacaterol provided 24 h bronchodilation on once-daily dosing with a fast onset of action. This study compared the efficacy and safety of indacaterol with the twice-daily LABA formoterol and placebo over 1 year. Methods: Patients with moderate to severe COPD were randomised to receive once-daily indacaterol 300 μg (n=437) or 600 μg (n=428), twice-daily formoterol 12 μg (n=435) or placebo (n=432) for 52 weeks in a double-blind double-dummy parallel group study. The primary efficacy variable was forced expiratory volume in 1 s (FEV1 ) measured 24 h postdose after 12 weeks (indacaterol vs placebo). Other outcomes included dyspnoea (transition dyspnoea index, TDI), use of as-needed salbutamol, symptom-based measures recorded on diary cards, exacerbations, health status (St George's Respiratory Questionnaire), BODE index (body mass index, obstruction, dyspnoea, exercise), safety and tolerability. Results: Indacaterol increased 24 h postdose FEV1 after 12 weeks by 170 ml (both doses) versus placebo and by 100 ml versus formoterol (all p<0.001). These significant differences were maintained at 52 weeks. Symptomatic outcomes were improved compared with placebo with all active treatments, and indacaterol was more effective than formoterol in improving TDI score and reducing the need for as-needed salbutamol. Indacaterol was well tolerated and had a good overall safety profile, including minimal impact on QTc interval and systemic β2 -mediated events. Conclusions: Once-daily indacaterol is an effective 24 h bronchodilator that improves symptoms and health status and confers clinical improvements over a twice-daily 12 h LABA as a treatment for patients with moderate to severe COPD. Trial registration number: NCT 00393458.